f(x) = 2x-3

g(x) = x+1

`f_og(3)` means that we get the value of f(x) when x = g(3)

g(x) = x+1

g(3) = 3+1 = 4

`f_og(3) ` = f(4) = 2(4)-3 = 5

`g_of(-2)` means that we get the value of g(x) when x = f(-2)

f(x) = 2x-3

f(-2) = 2*-2-3 = -7

`g_of(-2) ` = g(-7) = -7+1 = -6

*Therefore;*

`f_og(3) = 5`

*`g_of(-2) = -6` *

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now